2004
DOI: 10.1128/jcm.42.10.4432-4437.2004
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Observation Drug Susceptibility Assay, a Rapid, Reliable Diagnostic Test for Multidrug-Resistant Tuberculosis Suitable for Use in Resource-Poor Settings

Abstract: There is an urgent need for new tools to improve our ability to diagnose tuberculosis (TB) and multidrugresistant TB (MDR-TB) in resource-poor settings. In a retrospective analysis undertaken in a region with a high incidence of TB, we evaluated the performance of the microscopic observation drug susceptibility assay (MODS), a novel assay developed in Perú which uses an inverted light microscope and culture in Middlebrook 7H9 broth to detect mycobacterial growth. MODS detected 94.0% of 1,908 positive sputum cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(143 citation statements)
references
References 23 publications
6
132
1
4
Order By: Relevance
“…6,9 MODS, Microscopic Observation Drug Susceptibility assay, is a novel method for the diagnosis of TB infection and determination of susceptibility to anti-TB medications. This technique has been previously validated and shown to be quick and reliable [23][24][25][26] and has been implemented in the regional laboratories of the national TB program in Lima-Peru, 30,31 but otherwise has not been tested in the "field," in regional or district laboratories of low resource settings, for which it is intended. Demonstrating the ability to train laboratory technicians outside of research settings in developing countries to validly perform MODS, has been identified as a research priority.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,9 MODS, Microscopic Observation Drug Susceptibility assay, is a novel method for the diagnosis of TB infection and determination of susceptibility to anti-TB medications. This technique has been previously validated and shown to be quick and reliable [23][24][25][26] and has been implemented in the regional laboratories of the national TB program in Lima-Peru, 30,31 but otherwise has not been tested in the "field," in regional or district laboratories of low resource settings, for which it is intended. Demonstrating the ability to train laboratory technicians outside of research settings in developing countries to validly perform MODS, has been identified as a research priority.…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of MODS requires neither expensive equipment nor prepared special reagents. [22][23][24] The use of simple and available reagents addresses the problem of delivery of prepared supplied reagents to remote areas with a final cost for culture and susceptibility for one specimen of~2-3 US$. 21 We obtained positive culture results in 5-10 days (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth in the drug-containing wells and in the growth control is interpreted as resistance. MODS has been evaluated against first-line drugs although better results have been obtained for RIF and INH (Moore et al, 2004(Moore et al, , 2006. Although fairly accurate to detect resistance, especially to RIF, the requirement of an inverted microscope to read the plates and biosafety concerns related to the use of liquid medium in 24-well plates may hamper, however, its application outside large reference laboratories with the necessary logistic facilities.…”
Section: The Microscopic Observation Broth-drug Susceptibility Assay mentioning
confidence: 99%
“…[2][3][4][5][6] This method is based on the use of microtiter plates containing Middlebrook 7H10 liquid medium, with wells for controls as well as growth and AST of any isolates that grow. Specimens are processed prior to inoculation and the microtiter plates inoculated and incubated.…”
Section: Microscopic Observation Direct Susceptibility Assaymentioning
confidence: 99%